Supply chain integration and firm performance: the moderating role of demand uncertainty - Rosa Hendijani; Reza Saeidi Saei (Cogent Business & Management, 2020)
Supply chain integration (SCI) has become increasingly important among firms. Several studies have addressed SCI's effect on firm performance. However, many moderating factors such as demand uncertainty can influence its effect. In this study, we empirically examined the moderating effect of demand uncertainty on the relationship between SCI and firm performance. We developed a series of hypotheses to address these relationships. SCI was categorized into internal and external integration, with external integration divided into product and process integration. Rather than categorizing external integration into integration with suppliers and customers which was commonly used in previous studies, we used product and process integration as the categories for external integration. This allows us to have an integrated approach to all parties in the supply chain instead of separating the relationship with suppliers from that with customers. Study sample consists of firms active in automotive parts and steel industries in Iran. In total, 84 firms completed the survey. Hierarchical regression analysis was used to test research hypotheses. Industry type was considered as a control variable. Research findings showed that internal and process dimensions of integration had a positive effect on operational performance. In addition, internal and process dimensions had a positive effect on financial performance. In the face of high demand uncertainty, process integration improved financial performance. Moreover, industry type did not affect the results.
Keywords: 650; supply chain integration; demand uncertainty; performance